Writing after Kittler. - Koepnick, Lutz (German Studies Review, 2015)
The author discusses the work of German scholar Friedrich Kittler, with a focus on his views regarding writing in the computer era. Topics addressed include the idea of media philosophy as a methodology of German media theory, the concepts of software and hardware according Kittler, and the relationship between technology and civilization.